Linguagens lúdicas como estratégia metodológica para a geografia escolar na Revista do Ensino de Minas Gerais (1925-1935) - Dias, Angélica Mara de Lima (2013)
In this dissertation, we question the playful - while teaching methodology - in a historical perspective, using as a source of research the educational printed Revista do Ensino, published in Minas Gerais. Our focus stopped the methodological instructions presented by the aforementioned printed for the school Geography, addressing methodological strategies playful. The playful practices used as techniques for transmission of knowledge accompanying man since ancient times, when the games were meant to pass on the knowledge of the oldest to the youngest. With regard to the educational value, these practices are appropriate for Jesuit colleges in the sixteenth century. In the eighteenth century, the playful with educational value gains expressiveness to the work of the Swiss author Pestalozzi, from his intuitive method that prioritizes intuition and direct observation of the environment as a learning procedure. However, is with Froebel, disciple of Pestalozzi, and Montessori that the ludic as teaching methodology strengthens, defending the need of educational games for the education of each child's senses. The education of the senses criticizes the bookish education, focused on the words and memorization. This bias of thought gains greater visibility in the New School Movement, characterized by school renewal, especially with regard to the methodological practices. Agreeing with the importance of this movement to school, we believe that this has caused major changes starting from existing elements that began to acquire new meaning. Then we focus our attention to the 1920 and 1930 decades, frame time that marks the dissemination and integration of the first prescriptions and ideals of what would be called the New School. Thus, thinking the playful as teaching practice, we resorted to School Movement, in which the practice is valued by educators in the school environment. The school Geography as a discipline teaching was not out of the methodological innovations entered by the New School, and to expand our discussions on practices that use playful language in Geography, we turn to authors like Delgado de Carvalho and Élisée Reclus that, despite purposes completely antagonistic, appear quite ahead of their time, as well as external documents to Geography, in this particular case, the Magazine of Teaching from Minas Gerais.